SYSTEMATIC LITERATURE REVIEW: HUBUNGAN SISTEM INFORMASI AKUNTANSI DENGAN KINERJA PERUSAHAAN - Angga Praditya; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2022)
This study aims to identify the relationship between accounting information systems (AIS) and performance measurement based on published research articles. This study also aims to examine the diversity of results and patterns in terms of recommendations and contributions. Then, this study also explores gaps in science to develop future academic studies.This study uses a systematic literature review (SLR) method to analyze various articles published in academic journals indexed in the SCImago Journal Rank (SJR) published from 2011 to 2021, which focus on articles conducted in the Asia Pacific and Western Europe. Articles are filtered using defined keywords obtained from various top ranking journals. The SLR method is used to examine topics/themes, results, methodologies, recommendations, and limitations of published articles.The results of the analysis provide evidence that academic studies prove the importance of AIS in performance measurement related to technology selection, pressure from government regulations and competitors, and human resource considerations. Most companies define AIS in the form of enterprise resource planning (ERP), therefore ERP development always has appeal and becomes the focus of subsequent research. In terms of number, articles published in the Asia Pacific region dominate compared to Western Europe, meaning that there is a positive development in the application of AIS and academic studies in the Asia Pacific region. It was also found that the implementation of AIS had a positive impact on companies in various sectors and company scales.This finding is expected to provide substantial benefits to accounting information, developers in terms of ERP development in organizations and recommends exploring more about the environmental impact of using technology.